Study on species and biochemical composition of macro algae Gracilaria in Nghe An and Ha Tinh provinces - San, Nguyen Dinh; Tuan, Trinh Ngoc (Academia Journal of Biology, 2012)
Seven species and one subspecies of macro algae Gracilaria in the coat of Nghe An and Ha Tinh provinces were identificated in the period of the years 2008-2009. Among them Gracilaria tenuistipitata, Gracilaria tenuistipitata var. liu, Gracilariopsis bailina and Hydropuntia ramulosa there were four species which were biochemical analyzed by indexes as content of dry matter, content-ash, agar contents and content of deodorizing sugar. Their composition of fatty acids has been also reported. Palmitic acid (C16:0) revealed as the predominant component from 30 fatty acids discovered (31.43 - 44.50% of total fatly acid). The occurrence of unsaturated fatly acids (UFAs) is large quantity, high content and significantly different among macro algae species. There are 11 UFAs in G. tenuistipitata (occupying 37.92% of total fatly acids in this species), 7 UFAs G. tenuistipitata var. liu (91.66%); 15 UFAs in G. bailina (52.72%) and 15 UFAs in H. ramulosa (51.89%), respectively. Furthermore, the high bioactive fatly acids, such as eicosatetraenoic acid (AA, C20:4 n-6), eicosapentaenoic acid (EPA, C20:5 n-3), docosapentaenoic acid (DPA, C22:5 n-3) and arachidonic acid (ARA, C20:4 n-3), have been also discovered in the macro algae species. Remarkably, G. bailinae had significantly higher amounts of AA (16.28%) and EPA (28.98%), whereas H. ramulosa had AA levels of 29.09% compared with the total fatly acid content